2017
DOI: 10.1016/j.mce.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Early transcriptome responses of the bovine midcycle corpus luteum to prostaglandin F2α includes cytokine signaling

Abstract: In ruminants, prostaglandin F2alpha (PGF2α)-mediated luteolysis is essential prior to estrous cycle resumption, and is a target for improving fertility. To deduce early PGF2α-provoked changes in the corpus luteum a short time-course (0.5-4 h) was performed on cows at midcycle. A microarray-determined transcriptome was established and examined by bioinformatic pathway analysis. Classic PGF2α effects were evident by changes in early response genes (FOS, JUN, ATF3) and prediction of active pathways (PKC, MAPK). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 73 publications
5
38
0
Order By: Relevance
“…As in previous studies, changes in transcripts related to steroidogenesis, LH receptor signaling, and apoptosis were observed. Talbott et al (2017) also confirmed earlier studies in which progesterone declined prior to any decrease in transcripts related to steroidogenesis, and in which luteolysis was characterized by changes in transcripts related to cholesterol availability. However, most of these transcripts also changed coincident to, not before, the decrease in progesterone.…”
Section: Transcriptomic Profiling In the Corpus Luteumsupporting
confidence: 89%
“…As in previous studies, changes in transcripts related to steroidogenesis, LH receptor signaling, and apoptosis were observed. Talbott et al (2017) also confirmed earlier studies in which progesterone declined prior to any decrease in transcripts related to steroidogenesis, and in which luteolysis was characterized by changes in transcripts related to cholesterol availability. However, most of these transcripts also changed coincident to, not before, the decrease in progesterone.…”
Section: Transcriptomic Profiling In the Corpus Luteumsupporting
confidence: 89%
“…It was also found that NR4A1 can induce apoptosis by interacting with antiapoptotic proteins,50 suggesting that this factor can have additional roles in the porcine luteal tissue during regression. Interestingly, the expression of NR4A1 and couple other early response genes increase 30 minutes after PGF 2α injection in bovine midcycle corpus luteum, while 1.5 hours later plasma progesterone concentration decreases 52. Thus, we can conclude that NR4A1 with other early response genes acts on luteolytic changes occurring in the luteal tissue, which might be associated with dynamic post‐translational or post‐transcriptional modifications acutely inhibiting the function of the corpus luteum.…”
Section: Discussionmentioning
confidence: 79%
“… A complete list of differentially expressed transcripts grouped into self-organizing maps representative of signaling waves after PGF2α treatment. Canonical pathways and upstream regulators predicted by Ingenuity Pathway Analysis for genes common to three similar datasets [1] , [2] , [3] . …”
Section: Value Of the Datamentioning
confidence: 99%
“…Canonical pathways and upstream regulators predicted by Ingenuity Pathway Analysis for genes common to three similar datasets [1] , [2] , [3] .…”
Section: Value Of the Datamentioning
confidence: 99%
See 1 more Smart Citation